Novel prostate cancer susceptibility gene SP6 predisposes patients to aggressive disease - Sipeky Csilla; Tammela Teuvo L.J.; Auvinen Anssi; Schleutker Johanna (SPRINGERNATURE, 2022)
Prostate cancer (PrCa) is one of the most common cancers in men, but little is known about factors affecting its clinical outcomes. Genome-wide association studies have identified more than 170 germline susceptibility loci, but most of them are not associated with aggressive disease. We performed a genome-wide analysis of 185,478 SNPs in Finnish samples (2738 cases, 2400 controls) from the international Collaborative Oncological Gene-Environment Study (iCOGS) to find underlying PrCa risk variants. We identified a total of 21 common, low-penetrance susceptibility loci, including 10 novel variants independently associated with PrCa risk. Novel risk loci were located in the 8q24 (CASC8 rs16902147, OR 1.86, p(adj) = 3.53 x 10(-8) and rs58809953, OR 1.71, p(adj) = 4.00 x 10(-6); intergenic rs79012498, OR 1.81, p(adj) = 4.26 x 10(-8)), 17q21 (SP6 rs2074187, OR 1.66, p(adj) = 3.75 x 10(-5)), 11q13 (rs12795301, OR 1.42, p(adj) = 2.89 x 10(-5)) and 8p21 (rs995432, OR 1.38, p(adj) = 3.00 x 10(-11)) regions. Here, we describe SP6, a transcription factor gene, as a new, potentially high-risk gene for PrCa. The intronic variant rs2074187 in SP6 was associated not only with overall susceptibility to PrCa (OR 1.66) but also with a higher odds ratio for aggressive PrCa (OR 1.89) and lower odds for non-aggressive PrCa (OR 1.43). Furthermore, the new intergenic variant rs79012498 at 8q24 conferred risk for aggressive PrCa. Our findings highlighted the power of a population-stratified approach to identify novel, clinically actionable germline PrCa risk loci and strongly suggested SP6 as a new PrCa candidate gene that may be involved in the pathogenesis of PrCa.